EFFORTS TO INCREASE LEARNING MOTIVATION THROUGH GROUP GUIDANCE SERVICES USING GROUP DISCUSSION TECHNIQUES FOR STUDENTS OF SMPN 9 DENPASAR - I Nyoman Rajeg Mulyawan; I Gusti Ayu Agung Krisna Sudewi (Indonesian Journal of Educational Development (IJED), 2023)
This research was conducted at SMPN 9 Denpasar in class IX which has low learning motivation. This counseling guidance action research aims to determine whether Group Guidance Services with Group Discussion Techniques can increase student learning motivation. Research data on students' learning motivation was collected using a learning motivation questionnaire. Data were analyzed using percentage descriptive analysis. The obtained results in this study indicate an increase in student learning motivation from an initial average of 41%, increasing to 66% in cycle I and increasing to 90% in cycle II. The conclusion that can be drawn from these results is that the application of group guidance services with discussion techniques can increase student learning motivation.